Advanced Video Coding for Next-Generation Multimedia Services - Ho, Yo-Sung (IntechOpen, 2013)
This book aims to bring together recent advances and applications of video coding. All chapters can be useful for researchers, engineers, graduate and postgraduate students, experts in this area, and hopefully also for people who are generally interested in video coding. The book includes nine carefully selected chapters. The chapters deal with advanced compression techniques for multimedia applications, concerning recent video coding standards, high efficiency video coding (HEVC), multiple description coding, region of interest (ROI) coding, shape compensation, error resilient algorithms for H.264/AVC, wavelet-based coding, facial video coding, and hardware implementations. This book provides several useful ideas for your own research and helps to bridge the gap between the basic video coding techniques and practical multimedia applications. We hope this book is enjoyable to read and will further contribute to video coding.